dl-Tyrosinium chloride dihydrate - Guenifa, Fatiha (International Union of Crystallography, 2012)
In the title compound, C(9)H(12)NO(3) (+)·Cl(−)·2H(2)O, the cation has a protonated amino group resulting from proton transfer from chloridric acid. The structure displays double layers parallel to the [010] direction held together by N—H⋯O, N—H⋯Cl, O—H⋯O and O—H⋯Cl hydrogen bonds. These layers are stacked along the c axis at b = 1/2; within each layer, the tyrosinium cations are arranged in an alternating head-to-tail sequence, forming inversion dimers [R (2) (2)(10) motif]. The water molecules allow for the construction of a three-dimensional hydrogen-bonded network formed by centrosymmetric R (6) (6)(28) and R (8) (8)(34) motifs.